Fischer’s Fur Babies Veterinary Clinic - Fischer, Lucy (My University, 2022)
I have wanted to be a veterinarian for as long as I can remember. I was accepted into veterinary school as a senior in high school through Kansas State University College of Veterinary Medicine’s Early Admittance Program. Throughout my college journey, I’ve focused on Animal Science, Spanish, and Risk Management. For my Honors Project, I decided to combine my future entrepreneurial plans with my desire to help animals by designing my own veterinary practice. Since I am passionate about both private practice and shelter medicine, this plan combines the unique aspects of both. The idea for Fischer’s Fur Babies Veterinary Clinic came from my experience with the Animal Rescue Foundation in Chicago, IL. Seeing the impact that these foster organizations have on the lives of thousands of homeless animals fueled my desire to help make a difference. That is why our clinic is so focused on helping shelters and foster organizations. We are paying homage to the volunteers who dedicate their lives to this neverending work. This report details the key attributes of a veterinary clinic that bridges the gap between private practice and shelter medicine. It will explore different aspects of vertical integration and various activities the veterinary clinic will participate in to help better the lives of animals.